(untitled) (Research, Society and Development, 2021)
Osteonecrosis of the jaws related to medication use (OMRM) is a clinical situation, resulting from side effects of therapy with some drugs, such as bisphosphonates, RANK-L inhibitors and some antiangiogenics. The objective of the present work was to carry out a systematic review on OMRM. The research carried out allowed the selection of 9 articles, from 759 articles found. The results of the present study show that the most common underlying disease was breast cancer, the most prevalent route of administration was intravenous, tooth extraction was the main triggering dental procedure and the region most affected by the change was the mandible. The attendance by the dentist is essential before the beginning of the therapy with the studied drugs, mainly, with the bisphosphonates.